2000
DOI: 10.1111/1467-7687.00135
|View full text |Cite
|
Sign up to set email alerts
|

Children’s coding of human action: cognitive factors influencing imitaation in 3‐year‐old

Abstract: We used imitation as a tool for investigating how young children code action. The study was designed to examine the errors children make in re-enacting manual gestures they see. Thirty-two 3-year-old children served as subjects. Each child was shown 24 gestures, generated by systematically crossing four factors: visual monitoring, spatial endpoint, movement path, and number of hands. The results showed no difference as a function of whether the children could visually monitor their own responses. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
116
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 24 publications
16
116
1
Order By: Relevance
“…Other work also highlights the role of goals in imitation (Bekkering, Wohlschläger, & Gattis, 2000;Csibra & Gergely, 2007;Elsner, 2007;Gattis, Bekkering, & Wolschläger, 2002;Gleissner, Meltzoff, & Bekkering, 2000;Meltzoff & Moore, 1997;Tomasello et al, 2005;Williamson & Markman, 2006;Wohlschläger, Gattis, & Bekkering, 2003). Our work helps address developmental origins.…”
Section: Implications For Theorymentioning
confidence: 84%
“…Other work also highlights the role of goals in imitation (Bekkering, Wohlschläger, & Gattis, 2000;Csibra & Gergely, 2007;Elsner, 2007;Gattis, Bekkering, & Wolschläger, 2002;Gleissner, Meltzoff, & Bekkering, 2000;Meltzoff & Moore, 1997;Tomasello et al, 2005;Williamson & Markman, 2006;Wohlschläger, Gattis, & Bekkering, 2003). Our work helps address developmental origins.…”
Section: Implications For Theorymentioning
confidence: 84%
“…Indeed, recent research reveals that infants and children imitate what they perceive as the action's actual goal but not how this goal is reached in the particular situation [146,147,148]. For instance, if kids had watched an adult pressing a switch with her nose they will also tend to use their own nose to press the switch [149].…”
Section: Perceptual Primingmentioning
confidence: 99%
“…There is some reason to believe that infants may extend their goal bias to these events: Carpenter et al (2005) used Directed Motion events and found that infants preferentially enacted the goal of the event. Their study is not wholly compelling, however, as ii This objection cannot be leveled at all previously used events in this domain, in particular, the mirror game , Gleissner et al 2000 does not involve any functional changes. However, children's error rates (that is, their incorrect imitation of the ipsi-or contra-lateral hand motions) are not that high in this game, topping out at around 25%.…”
mentioning
confidence: 94%